Is the Level of Noise in a School Environment be Harmful to the Hearing of Teachers? - Novanta,Gabriela Guenther Ribeiro (2020)
Abstract Introduction The excessive noise observed in the school environment can cause damages or losses to the learning process as well as risks to the health of teachers and students, such as physical, mental and social impairments, including, among them, hearing loss. Objective To assess otoacoustic emissions in teachers and determine whether classroom noise reduces distortion-product otoacoustic emissions (DPOAEs) amplitude and signal-to-noise ratio (SNR). Method Sixty-seven teachers were evaluated using otoacoustic emissions testing in two situations: after hearing rest and after the working day. Results Signal amplitude (p = 0.044 [2 kHz]; p = 0.01 [4 kHz]) and SNR for frequencies of 2 kHz (p = 0.008) and 4 kHz (p = 0.001) decreased significantly between time points. Mean classroom noise was associated with the magnitude of the difference in signal amplitude at 2 kHz (p = 0.017) and 4 kHz (p = 0.015), and SNR at 4 kHz (p = 0.023). Conclusions There was a decrease in the amplitude and in the SNR after exposure to the noise in the classroom environment. The high levels of sound pressure that teachers are exposed to on a daily basis can cause a temporary change in the outer hair cells of the Corti organ, and these changes may become permanent over time.